PERAN CORPORATE GOVERNANCE TERHADAP EARNINGS MANAGEMENT PADA FAMILY FIRMS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2016 - Chelsea Giovani Halim; Yie Ke Feliana (Perpustakaan Universitas Surabaya, 2018)
Abstract - This study aims to determine the role of corporate governance to earnings management in Indonesian family firms. This research uses quantitative approach and tested with multiple linear regression model. The object of this research is all companies listed in Indonesia Stock Exchange (BEI) except financial sector for the period of 2016. The amount of sample used in this research is 301 companies. The dependent variable used is abnormal accruals. While the independent variable used is family firms. Corporate governance in this study focuses on the composition of the board of commissioners and audit committee. The results of this study indicate that corporate governance can’t affect earnings management in family firms. Both family firm and non-family firm have the same ability and opportunity to earn earnings management. Companies in Indonesia still have not implemented good corporate governance. Earnings management may decrease along with increased leverage, sales growth, and operating cash flow.